PERAN IBU DALAM MENANAMKAN ETIKA MAKAN PADA ANAK USIA DINI MENURUT ISLAM - Syakira, Astri (Universitas PGRI Palembang, 2024)
This study was conducted to find out about the role of mothers in instilling eating ethics in early childhood according to Islam. The data from this study were collected through analysis and observation and using literature methods. The purpose of the study was to discuss how mothers teach eating ethics to children with Islamic teachings, get children used to good and correct eating ethics, and reprimand (conflict mediator) children when they waste food. This really needs to be discussed and studied to find out what role mothers play in instilling eating ethics in early childhood according to Islam.